2018
DOI: 10.1007/s11205-018-1887-2
|View full text |Cite
|
Sign up to set email alerts
|

Online Social Networks and Trust

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 70 publications
1
21
0
Order By: Relevance
“…The first two studies on online networks and trust that were carried out after the advent of Facebook and other online social networks, however, reached opposing results and pointed out the need to further investigate how the use of SNS relates to social capital and well‐being. Sabatini and Sarracino () found that the use of SNS is significantly and negatively correlated with trust in unknown others and in public institutions in Italy for the period 2010‐11. Antoci et al () explained the possibly detrimental effects of the use of SNS as a consequence of online incivility, a widespread phenomenon including aggressive and disrespectful behaviors, vile comments, harassment, and hate speech that makes online social environments potentially hostile for users (Rainie et al, ; Duggan, ).…”
Section: Sns and Social Capitalmentioning
confidence: 99%
“…The first two studies on online networks and trust that were carried out after the advent of Facebook and other online social networks, however, reached opposing results and pointed out the need to further investigate how the use of SNS relates to social capital and well‐being. Sabatini and Sarracino () found that the use of SNS is significantly and negatively correlated with trust in unknown others and in public institutions in Italy for the period 2010‐11. Antoci et al () explained the possibly detrimental effects of the use of SNS as a consequence of online incivility, a widespread phenomenon including aggressive and disrespectful behaviors, vile comments, harassment, and hate speech that makes online social environments potentially hostile for users (Rainie et al, ; Duggan, ).…”
Section: Sns and Social Capitalmentioning
confidence: 99%
“…Education generates social capital in various ways, as students become familiar with the social norms of their profession or specialty, so the adult part of the population is better socialized. In the case of individual companies, social capital can be cultivated deliberately through direct investment in education and corporate skills training, which is a way of socializing company employees through a set of norms that increase the willingness to cooperate with each other 210, 17034 (2020) E3S Web of Conferences ITSE-2020 https://doi.org/10.1051/e3sconf/202021017034 and generate a sense of group identity (Fabio Sabatini, Francesco Sarracino, 2018 [13]; Joseph A. Hamm, Corwin Smidt, Roger C. Mayer 2019, [14]).…”
Section: Resultsmentioning
confidence: 99%
“…Authors suggested that trusted and untrusted information providers should be classified and proposed the use of kanonymity technique for information disclosure. Users depend on OSNs for interaction among their groups [36], [56], [57]. Basic four things that invite spammers are (i) controlling entity of the entire OSN (ii) well-defined interactions (iii) user Identity (iv) multiple interfaces of OSN providing different views [44].…”
Section: Privacy Leaks and Privacy Measures In Osnsmentioning
confidence: 99%